2013
DOI: 10.1002/jbm.a.34912
|View full text |Cite
|
Sign up to set email alerts
|

The effect of active ingredient‐containing chitosan/polycaprolactone nonwoven mat on wound healing: In vitro and in vivo studies

Abstract: The use of an electrospun polycaprolactone (PCL) nonwoven mat that is coated with a layer of chitosan (CS) containing active ingredient [tea tree oil (TTO)] represents an effective strategy for producing functional dressings. CS-coated porous PCL nonwoven mat (CS3/PCLNM) with various concentrations of active ingredients were produced and investigated. In vitro, active ingredient-containing CS3/PCLNM is effective in inhibiting the formation of nitrite and the growth of Staphylococcus aureus. Both active ingredi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…There are encouraging data for the treatment of wound infections with tea tree EO integrated into various functional dressings. For example, an electrospun polycaprolactone (PCL) nonwoven mat covered with a layer of chitosan and containing tea tree EO were produced and investigated in vitro [ 113 ]; tests proved that the mat effectively inhibited the growth of S. aureus . In vivo tests were performed by skin subtraction having dimensions of (1.2 × 1.2) cm 2 on the back of the C57BL6/J mice in non-infected and infected animal models.…”
Section: Antibacterial Agents In Wound Dressingsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are encouraging data for the treatment of wound infections with tea tree EO integrated into various functional dressings. For example, an electrospun polycaprolactone (PCL) nonwoven mat covered with a layer of chitosan and containing tea tree EO were produced and investigated in vitro [ 113 ]; tests proved that the mat effectively inhibited the growth of S. aureus . In vivo tests were performed by skin subtraction having dimensions of (1.2 × 1.2) cm 2 on the back of the C57BL6/J mice in non-infected and infected animal models.…”
Section: Antibacterial Agents In Wound Dressingsmentioning
confidence: 99%
“…In vivo tests were performed by skin subtraction having dimensions of (1.2 × 1.2) cm 2 on the back of the C57BL6/J mice in non-infected and infected animal models. After 7 days post-treatment, bacterial levels were found to be lower for the nonwoven mat with 10 μL concentration of tea tree EO-treated groups than the control: 81.6 ± 18.1% and 93.7 ± 9.57% decrease of bacterial contents, as compared to the control group [ 113 ]. Other studies synthesized films of chitosan loaded with different contents of tea tree EO droplets.…”
Section: Antibacterial Agents In Wound Dressingsmentioning
confidence: 99%
“…Polyethylene oxide (PEO) [110,111] Loss of mechanical properties can occur very early during degradation [104] Polycaprolactone (PCL) [112,113] Polyvinyl alcohol (PVA) [112,114,115] Polyurethane (PU) [116,117] Polystyrene (PS) [118] Many materials present native biomolecular signals associated with cell binding/proliferation/migration and immune responses [77,103] Processing can induce denaturation [77] Collagen [107,119] Harvesting and processing can be complex [45] Gelatin [120][121][122] Sources of biopolymers, purity, and molecular weight distribution can influence process properties and resulting architecture of meshes. Risk of disease transmission and possible antigenicity [45] Chitosan [110,113,115] Fibrinogen [123] Hyaluronic acid [48,124] Cellulose [125][126][127] Electrospun Nanofibers as Dressings for Chronic Wound Care . .…”
Section: Some Materials Can Release Toxic Degradation Productsmentioning
confidence: 99%
“…However, the shortcomings of PCL, such as its slow degradation, strong hydrophobicity and lack of bioactive functions have greatly restricted its employment in tissue engineering. Recently, to combine the high plasticity and strength of PCL and the excellent biological properties of CS, some researchers have attempted to blend the CS and PCL for wound healing, vascular graft, retinal or cartilage tissue regeneration and showed that the CS/PCL composition could support the proliferation of endothelial cells, promote wound healing and tissue regeneration [11][12][13][14][15] . Particularly, some studies found that PCL/CS scaffolds containing 20% chitosan prepared by melt stretching and multilayer deposition (MSMD) technique had rather low efficacy for repairing bone defects 13) , while other studies showed that scaffolds with a shish-kebab (SK) structure formed by poly(ε-caprolactone) (PCL) nanofibers and chitosan-PCL (CS-PCL) copolymers had good potential for bone tissue engineering 16) .…”
Section: Introductionmentioning
confidence: 99%